Komunikasi Dalam Perspektif Agama Hindu - Wayan Ngurah Eka Kurniawan (Pramana: Jurnal Hasil Penelitian, 2021)
Hindu communication has been considered a new discipline in the field of communication theory and practice. This does not mean that the seeds or ideas of communication have not existed in the literature and practice since the Vedic period. References taken from the fields of poetry, aesthetics, and drama in Sanskrit literature show that there are many sources that can be used as the main sources for developing a proper Hindu communication system. Sadharanikarakana as a generalization theory in poetic expression was developed into a Hindu communication model in the modern era. The model consists of several aspects, such as sahridaya (parties involved - sender and receiver), sahridayata (state of equality), bhava (mood), abhivyanjana (encoding), sandesha (message), Sarani (channel), rasawadana (first received, decoding and interpreting the message and finally reaching the taste), dosha (voice), and pratikriya (feedback); they become the gift of the whole system. As a communication model, each party involved in the communication process tries to achieve a state of unity, similarity, generality, universality called sahridayata. With this situation, any differences in various areas of life can be transcended into mutual understanding because unity or similarity has been achieved through the process of negotiating meaning. In the realm of oneness the trans-empirical truth (advaita) with the Ultimate Reality (called Brahman) is in the form of rasa